Guide to Fiber Supplements - Wendy J. Dahl (EDIS)
Constipation is a common health concern that is commonly caused by low fiber intake. This 2-page fact sheet provides answers to common questions about fiber supplements. Written by Wendy J. Dahl. Published by the UF Department of Food Science and Human Nutrition, January 2011.